Retrospective review of management of diabetic retinopathy in pregnant diabetics at Hospital Universiti Kebangsaan Malaysia - Noor Aniah, A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Diabetic retinopathy (DR) may progress when diabetic women pregnant. It is clear that DR cases are increasing around the world and the danger is alarming. This is a retrospective case with 168 pregnant patients which were traced from the registry held by Endocrine Antenatal Clinic, Department of Obstetrics and Gynaecology, Universiti Kebangsaan Malaysia Medical Centre from 2016 to 2019. Of the 138 pregnancies in pre-existing diabetics, 97 records (70.3%) were found to have only one follow-up with incomplete ophthalmology records or defaulters. Only 41 pregnancy records (29.7%) completed with at least two ophthalmology reviews during the pregnancy. Progression of DR was noted in seven of these pregnancies, giving a rate of 17.0%. One eye of one patient progressed from mild non-proliferative DR to sight-threatening proliferative DR (PDR). When comparing the group of progressors with non-progressors, there was no statistically significant difference for risk factors (age, gender, ethnicity, type of diabetes, duration of diabetes, HbA1c level, hypertension, presence of maculopathy, risk factors for diabetes and fetal ultrasound findings). The rate of repeated follow-up for retinopathy during pregnancy in diabetics is about 30%. This study suggested that no risk factors were identified for DR progression.